2000
DOI: 10.1210/jcem.85.11.6991
|View full text |Cite
|
Sign up to set email alerts
|

Expression of the Thyroid-Stimulating Hormone Receptor in the Folliculo-Stellate Cells of the Human Anterior Pituitary

Abstract: TSH secretion from the anterior pituitary is mainly regulated by TRH and thyroid hormones. We hypothesized that in addition the pituitary itself could modulate TSH production by sensing its own TSH release, enabling fine-tuning of TSH secretion. For such an ultra-short loop control, the pituitary should contain a TSH receptor (TSH-R). To find evidence for this we screened a human pituitary complementary DNA library with a digoxigenin-labeled TSH-R probe and found 2 positive clones of 32,000 plaques. One clone … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
39
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(44 citation statements)
references
References 29 publications
(31 reference statements)
4
39
0
Order By: Relevance
“…4). The expression of the TSH receptor reported earlier in MHC-class II cells (40) and the increase in D2 activity that has been observed in TSH-producing tumors (41) suggests that D2 expression in the anterior pituitary can be influenced directly by TSH. This is further supported by a dose-dependent increase of D2 mRNA by TSH, which has been reported in human thyroid cells and the presence of a cAMP response element in the D2 promoter (42).…”
Section: Discussionmentioning
confidence: 63%
“…4). The expression of the TSH receptor reported earlier in MHC-class II cells (40) and the increase in D2 activity that has been observed in TSH-producing tumors (41) suggests that D2 expression in the anterior pituitary can be influenced directly by TSH. This is further supported by a dose-dependent increase of D2 mRNA by TSH, which has been reported in human thyroid cells and the presence of a cAMP response element in the D2 promoter (42).…”
Section: Discussionmentioning
confidence: 63%
“…Moreover, the detection in vitro of numerous receptors in FS cells (15) or TtT/GF cells (93 -95), as well as of [Ca 2þ ] i rises in response to certain stimuli (94), further point to the 'excitable' nature of these cells. On the other hand, the occurrence of TSH receptors in a subpopulation of FS cells also expressing MHC-class II receptors (29) points to a possible role of these receptors in the immune accessory function of this FS cell subpopulation. Functional TSH receptors are also found in TtT/GF cells; these, however, are not coupled to cAMP or inositol 1,4,5-triphosphate pathways, but probably signal through the Janus kinase/signal transducer and activator of transcription 5a pathway (30).…”
Section: New Perspectives In Fs Cell Physiologymentioning
confidence: 99%
“…This electrically coupled FS cell network was suggested to provide a mechanism for long-distance communication in the anterior pituitary in response to physiological stimuli (28). The finding of thyrotropin (TSH) receptors expressed in a subpopulation of FS cells in situ and in cell lines also opened a new perspective on ultra-short feedback loop regulation by FS cells of TSH secretion (29,30).…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies proposed different causes of transient suppressed serum TSH level during antithyroid drug therapy. Prummel et al (2000) reported that TSH receptor was expressed in the folliculo-stellate (FS) cells of the human anterior pituitary gland, and TSH secretion might be down regulated through TSH receptor via a paracrine feedback loop (8). Delayed recovery of pituitarythyroid axis may be also from long standing thyroid hormone excess (9).…”
Section: Discussionmentioning
confidence: 99%